Targeting C-Reactive Protein in Inflammatory Disease by Preventing Conformational Changes - J. R. Thiele; J. Zeller; H. Bannasch; G. B. Stark; K. Peter; S. U. Eisenhardt (Mediators of Inflammation)
C-reactive protein (CRP) is a pentraxin that has long been employed as a marker of inflammation in clinical practice. Recent findings brought up the idea of CRP to be not only a systemic marker but also a mediator of inflammation. New studies focused on structural changes of the plasma protein, revealing the existence of two distinct protein conformations associated with opposed inflammatory properties. Native, pentameric CRP (pCRP) is considered to be the circulating precursor form of monomeric CRP (mCRP) that has been identified to be strongly proinflammatory. Recently, a dissociation mechanism of pCRP has been identified on activated platelets and activated/apoptotic cells associated with the amplification of the proinflammatory potential. Correspondingly, CRP deposits found in inflamed tissues have been identified to exhibit the monomeric conformation by using conformation-specific antibodies. Here we review the current literature on the causal role of the dissociation mechanism of pCRP and the genesis of mCRP for the amplification of the proinflammatory potential in inflammatory reactions such as atherosclerosis and ischemia/reperfusion injury. The chance to prevent the formation of proinflammatory mediators in ubiquitous inflammatory cascades has pushed therapeutic strategies by targeting pCRP dissociation in inflammation. In this respect, the development of clinically applicable derivatives of the palindromic compound 1,6-bis(phosphocholine)-hexane (1,6-bis PC) should be a major focus of future CRP research.